Carbapenemases in Klebsiella pneumoniae and Other Enterobacteriaceae: an Evolving Crisis of Global Dimensions - Tzouvelekis, L. S. (American Society for Microbiology, 2012)
Summary: The spread of Enterobacteriaceae, primarily Klebsiella pneumoniae, producing KPC, VIM, IMP, and NDM carbapenemases, is causing an unprecedented public health crisis. Carbapenemase-producing enterobacteria (CPE) infect mainly hospitalized patients but also have been spreading in long-term care facilities. Given their multidrug resistance, therapeutic options are limited and, as discussed here, should be reevaluated and optimized. Based on susceptibility data, colistin and tigecycline are commonly used to treat CPE infections. Nevertheless, a review of the literature revealed high failure rates in cases of monotherapy with these drugs, whilst monotherapy with either a carbapenem or an aminoglycoside appeared to be more effective. Combination therapies not including carbapenems were comparable to aminoglycoside and carbapenem monotherapies. Higher success rates have been achieved with carbapenem-containing combinations. Pharmacodynamic simulations and experimental infections indicate that modification of the current patterns of carbapenem use against CPE warrants further attention. Epidemiological data, though fragmentary in many countries, indicate CPE foci and transmission routes, to some extent, whilst also underlining the lack of international collaborative systems that could react promptly and effectively. Fortunately, there are sound studies showing successful containment of CPE by bundles of measures, among which the most important are active surveillance cultures, separation of carriers, and assignment of dedicated nursing staff.